Involvement of metallothionein (MT) as a biological protective factor against carcinogenesis induced by benzo[a]pyrene (B[a]P). - Takaishi, M; Shimada, A; Suzuki, J; Satoh, M; Nagase, H (2010)
The purpose of this study was to examine whether intracellular metallothionein (MT) protects against benzo[a]pyrene (B[a]P)-induced forestomach and lung carcinogenesis. Ten-week-old male MT-I/II null mice and wild-type mice were orally administered B[a]P at a dose of 100 or 250 mg/kg twice a week for 4 weeks. B[a]P-induced mortality was higher in the MT-I/II null mice than in the wild-type mice. The incidence of tumors in the forestomach and lung was 78.6% and 7.1% in the wild-type mice treated with 100 mg/kg B[a]P, respectively. In the MT-I/II null mice treated with B[a]P, tumor incidence in the forestomach and lung was 100% and 33.3%, respectively. The tumor area in the forestomach and lung in the MT-I/II null mice treated with B[a]P was greater than that of wild-type mice. These results suggest that MT acts as a biological protective factor against carcinogenesis induced by B[a]P.